PENGARUH PENDAPATAN PEDAGANG, JARAK TEMPUH, DAN TATA LETAK KOTA TERHADAP REVITALISASI PASAR BITINGAN KABUPATEN KUDUS DALAM PERSPEKTIF ISLAM - Maulida Azzahra, Lailatul; Eni Kusrini (Universitas Ratu Samban, 2023)
The background of this research is the Bitingan market revitalization activities in Kudus Regency, where there are inconsistencies that affect market revitalization, which can be seen from the income level of traders, distance traveled, and city layout. The existence of this indicator shows the need for further research on the revitalization of the Bintingan market in Kudus Regency. In this study the aims were to find out, analyze, explain the effect of the revitalization of the Biningan market in Kudus Regency. The type of research used is descriptive quantitative research which is complemented by primary data through a questionnaire or questionnaire using a Likert scale. The data analysis technique used in this research is Descriptive Statistical Test, Validity Test and Reliability Test, Multiple Regression Test including Classical Assumption Test and Hypothesis Test. The results of the three tests show that at the income level of traders it tends to be positive but not significant, mileage is not significant negative while the layout of the city tends to be negative and significant meaning that the revitalization of the Bitingan market in Kudus Regency is very vulnerable to social phenomena with many problems that occur during the revitalization of the Bitingan market.